Rare exonic CELSR3 variants identified in Bladder Exstrophy Epispadias Complex - Jelin, Angie C.; Sopko, Nikolai; Sobreira, Nara; Boyadjiev, Simeon A.; Wohler, Elizabeth; Morrill, Christian; Witmer, P. Dane; Michaud, Jason; Valle, David; Gearhart, John; Dicarlo, Heather (Frontiers in Genetics, 2024)
Introduction/background Bladder exstrophy epispadias complex (BEEC) is a rare congenital anomaly of unknown etiology, although, genetic and environmental factors have been associated with its development. Variants in several genes expressed in the urogenital pathway have been reported as causative for bladder exstrophy in human and murine models. The expansion of next-generation sequencing and molecular genomics has improved our ability to identify the underlying genetic causes of similarly complex diseases and could thus assist with the investigation of the molecular basis of BEEC. Objective The objective was to identify the presence of rare heterozygous variants in genes previously implicated in bladder exstrophy and correlate them with the presence or absence of bladder regeneration in our study population. Patients and Methods We present a case series of 12 patients with BEEC who had bladder biopsies performed by pediatric urology during bladder neck reconstruction or bladder augmentation. Cases were classified as “sufficient” or “insufficient” (n = 5 and 7, respectively) based on a bladder volume of greater than or less than 40% of expected bladder size. Control bladder tissue specimens were obtained from patients (n = 6) undergoing biopsies for conditions other than bladder exstrophy. Whole exome sequencing was performed on DNA isolated from the bladder specimens. Based on the hypothesis of de novo mutations, as well as the potential implications of autosomal dominant conditions with incomplete penetrance, each case was evaluated for autosomal dominant variants in a set of genes previously implicated in BEEC. Results Our review of the literature identified 44 genes that have been implicated in human models of bladder exstrophy. Our whole exome sequencing data analysis identified rare variants in two of these genes among the cases classified as sufficient, and seven variants in five of these genes among the cases classified as insufficient. Conclusion We identified rare variants in seven previously implicated genes in our BEEC specimens. Additional research is needed to further understand the cellular signaling underlying this potentially genetically heterogeneous embryological condition.